2021
DOI: 10.1186/s12968-021-00781-w
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous assessment of myocardial injury with single-shot model-based non-rigid motion-corrected T1 rho mapping

Abstract: Background Cardiovascular magnetic resonance T1ρ mapping may detect myocardial injuries without exogenous contrast agent. However, multiple co-registered acquisitions are required, and the lack of robust motion correction limits its clinical translation. We introduce a single breath-hold myocardial T1ρ mapping method that includes model-based non-rigid motion correction. Methods A single-shot electrocardiogram (ECG)-triggered balanced steady state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…27 Furthermore, Bustin et al have found a +40% elevation in infarcted myocardium of LGE-positive patients. 29 These trends are in agreement with the T 1ρ,adiab enhancement measured in patient 1. On the other hand, T 1ρ,adiab in the scar area of patient 2 was decreased.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…27 Furthermore, Bustin et al have found a +40% elevation in infarcted myocardium of LGE-positive patients. 29 These trends are in agreement with the T 1ρ,adiab enhancement measured in patient 1. On the other hand, T 1ρ,adiab in the scar area of patient 2 was decreased.…”
Section: Discussionsupporting
confidence: 88%
“…28,64,65 Furthermore, several motion correction approaches have been proposed to improve the quality of reconstructed T 1ρ maps and mitigate the contribution of motion. 26,29 These efforts are key to enabling the widespread use of quantitative parametric mapping sequences in clinical practice. Our aSL preparations are fully compatible with these sequence designs and reconstruction approaches and could, in the future, be integrated into accelerated and motion-corrected T 1ρ mapping sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of non-contrast T1 ρ -mapping in CMR has been reported to discriminate between infarcted and healthy myocardium in animal models (97). Oedema also induces enhancement in T1 ρ values, as demonstrated in the area-at-risk in acutely ischemic myocardium, in acute myocarditis and Takotsubo cardiomyopathy (98,99). This mapping technique sequence is yet to be routinely used in clinical practice.…”
Section: T1 ρ Mappingmentioning
confidence: 99%
“…In the first work package, novel CMR sequences will enable 3D imaging of cardiac anatomy and function (cine), cardiac tissue mapping (T1/T2/T1-rho/extracellular volume fraction), and myocardial scars (with joint bright- and black-blood imaging) with minimal scan planning and patient cooperation. 9 , 10 The uninterrupted fashion of the sequences will eliminate the need for multiple highly specialized scans, whereas the black-blood technology will provide unprecedented contrast for automated analysis of myocardial injuries. In work package 2, the consortium will exploit the co-registered contrasts to automatically extract healthy and injured cardiac tissue parameters.…”
mentioning
confidence: 99%